Novel Janus GaInX3 (X = S, Se, Te) single-layers: first-principles prediction on structural, electronic, and transport properties. Issue 13 (11th March 2022) - Vu, Tuan V.; Hieu, Nguyen N.; Lavrentyev, A. A.; Khyzhun, O. Y.; Lanh, Chu V.; Kartamyshev, A. I.; Phuc, Huynh V.; Hieu, Nguyen V.
Abstract : In this paper, the structural, electronic, and transport properties of Janus GaInX3 (X = S, Se, Te) single-layers are investigated by a first-principles calculations. Abstract : In this paper, the structural, electronic, and transport properties of Janus GaInX3 (X = S, Se, Te) single-layers are investigated by a first-principles calculations. All three structures of GaInX3 are examined to be stable based on the analysis of their phonon dispersions, cohesive energy, and Born's criteria for mechanical stability. At the ground state, The Janus GaInX3 is a semiconductor in which its bandgap decreases as the chalcogen element X moves from S to Te. Due to the vertical asymmetric structure, a difference in the vacuum level between the two surfaces of GaInX3 is found, leading to work functions on the two sides being different. The Janus GaInX3 exhibit high directional isotropic transport characteristics. Particularly, GaInX3 single-layers have high electron mobility, which could make them potential materials for applications in electronic nanodevices.